2016
DOI: 10.1016/j.vaccine.2015.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Status of vaccine research and development of vaccines for leishmaniasis

Abstract: A number of leishmaniasis vaccine candidates are at various stages of pre-clinical and clinical development. Leishmaniasis is a vector-borne neglected tropical disease (NTD) caused by a protozoan parasite of the genus Leishmania and transmitted to humans by the bite of a sand fly. Visceral leishmaniasis (VL, kala-azar) is a high mortality NTD found mostly in South Asia and East Africa, while cutaneous leishmaniasis (CL) is a disfiguring NTD highly endemic in the Middle East, Central Asia, North Africa, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
145
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(148 citation statements)
references
References 25 publications
2
145
0
1
Order By: Relevance
“…In an attempt to control the disease, many strategies are used to interrupt parasite transmission, including elimination of seropositive dogs that act as reservoirs, use of insecticides for vector control and systematic treatment of human cases (3, 4). Several studies have shown the importance of the development of vaccines to control the disease (58); however, to date there are no vaccines that can be used in control programs against human or canine disease (9). Moreover, available treatment options are still far from a desirable efficacy due the fact that they are either toxic (antimonials and amphotericin B deoxycholate) or expensive (liposomal amphotericin B) (10).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to control the disease, many strategies are used to interrupt parasite transmission, including elimination of seropositive dogs that act as reservoirs, use of insecticides for vector control and systematic treatment of human cases (3, 4). Several studies have shown the importance of the development of vaccines to control the disease (58); however, to date there are no vaccines that can be used in control programs against human or canine disease (9). Moreover, available treatment options are still far from a desirable efficacy due the fact that they are either toxic (antimonials and amphotericin B deoxycholate) or expensive (liposomal amphotericin B) (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, many leishmaniasis candidate vaccines (recombinant protein-based and DNA-based vaccines) are at various stages of preclinical and clinical development [4]. Among them, Leish-111 is currently under phase II clinical trials [5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no vaccination is available against leishmaniasis (7). There is a continuous and gradual increase in the prevalence of drug-resistant Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%